The relationship between training load and pain, injury and illness in competitive swimming: A systematic review - Barry, L.; Lyons, M.; McCreesh, K.; Powell, C.; Comyns, T. (Physical Therapy in Sport, 2021)
Highlights: • Internal training load monitoring should be included in competitive swimming environments consistent with IOC guidelines.